PERENCANAAN TARIF ANGKUTAN UMUM JURUSAN PALANGKA RAYA – TUMBANG HIRAN DALAM MASA PANDEMI ( COVID-19 ) (Planning Of Public Transport Rates Palangka Raya Department – Tumbang Hiranduring A Pandemic ( Covid-19 ) - Aria Hansen; Robot . (Fakultas Teknik Universitas Kristen Palangka Raya, 2022)
The public force is a means of transportation needed by most urban/regional people, it is impossible for a city/region to live without public transportation. Taxi public transportation is one of the alternative public transportation in the district area, which provides other services and is not the same as other transportation. The purpose of this study is to determine the amount of Vehicle Operating Costs (BOK) for public transportation from Palangka Raya City to Tumbang Hiran Village, as well as to find out the amount of passenger fares in accordance with the Vehicle Operational Costs (BOK) issued. Based on the results of the analysis of Vehicle Operational Costs (BOK), the total basic costs per day for general passengers for the City of Palangka Raya Towards Tumbang Hiran Village are: Innova cars of Rp. Hiran is Rp. 150,305.28/person/trip. The basic fare for public transportation heading from Palangka Raya City to Tumbang Hiran Village is IDR 165,335.66/org/rit. While the tariff at the time this research was conducted was Rp. 350,000 total revenue per day at a rate of Rp. 350,000 x the number of trips per day was Rp. 1,400,000 / person / person. The two transportation vehicles above provide a decent opinion for the manager / owner For passengers, the price is reasonable, feasible and affordable because it is in accordance with the time and distance traveled. Keywords: Public Transportation / Taxi, Vehicle Operational Cost (BOK) per km, Total cost